Application of cluster nursing management in enteral nutrition of critically ill patients (集束化护理管理在危重症患者肠内营养中的应用) - LIU Ai (刘爱); YAN Hong (颜红); TONG Lu (佟璐) (Association of Integrative Nursing, 2023)
The application of enteral nutrition therapy is one of the important therapeutic measures during the treatment of critically ill patients. In this paper, the interventions of cluster nursing management for patients with enteral nutrition was described in perspectives of risk screening, nutrition assessment, pipeline nursing, nutrient solution configuration, complication prevention, and the operation standard and implementation of the process management were clarified, in order to provide reference for the further optimization of enteral nutrition nursing process in clinical practice. (肠内营养(EN)是危重症患者营养支持的重要治疗性措施之一。本文阐述了肠内营养患者集束化护理干预方法, 包含风险筛查、营养评估、管路的护理、营养液配置、并发症的预防等, 明确操作规范和实施的过程管理, 以期为EN护理流程的进一步优化提供参考。)